2013
DOI: 10.1016/j.clp.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Short Bowel Syndrome in the NICU

Abstract: Short bowel syndrome (SBS) is the most common cause of intestinal failure in infants. In neonates and young infants, necrotizing enterocolitis, gastroschisis, intestinal atresia and intestinal malrotation/volvulus are the leading causes of SBS. Following an acute post-surgical phase, the residual gastrointestinal tract adapts with reorganization of the crypt-villus histoarchitecture and functional changes in nutrient absorption and motility. A cohesive, multidisciplinary approach can allow most neonates with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 84 publications
(135 reference statements)
1
77
0
12
Order By: Relevance
“…Therefore the reported case is certainly of great interest in view of the patient's capacity to survive for many years after massive resection of the small intestine, despite several associated negative prognostic factors. 12,13 To our knowledge, previously studies have already reported cases of subjects with residual intestines of lengths ranging from 11 to 13 cm. who survived in good clinical condition, but in all these cases the ileocecal valve had been spared, and PN support could not be eliminated in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the reported case is certainly of great interest in view of the patient's capacity to survive for many years after massive resection of the small intestine, despite several associated negative prognostic factors. 12,13 To our knowledge, previously studies have already reported cases of subjects with residual intestines of lengths ranging from 11 to 13 cm. who survived in good clinical condition, but in all these cases the ileocecal valve had been spared, and PN support could not be eliminated in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…If sodium losses are not adequately replaced, compensatory hyperaldosteronism can arise, and as a result, an increase in urinary potassium loss can occur. 11,12 Although parenteral nutrition is of major importance for the management of surgical infants when there is need to bypass the gastrointestinal tract to provide nutrition and fluids, its use is associated with significant complications, such as the previously mentioned intestinal failure-associated liver disease, catheter malfunction and the development of catheter-related bloodstream infections and/or thrombosis. Hence, parenteral nutrition volume should be gradually reduced to discontinuation as soon as a slow and carefully monitored enteral nutrition approach can be implemented.…”
Section: Parenteral Nutritionmentioning
confidence: 99%
“…However, it must be taken into account that, in addition to the reduction of the intestinal length, impaired intestinal function may coexist, further contributing to inadequate absorption of enteral nutrients. 11,12,23,35 In Table 1 most common causes of short bowel syndrome in newborns and infants are indicated. The frequency of surgical short bowel syndrome was reported to be 0.7% among very low birth weight infants born during the period from 2002 to 2005 at the National Institute of Child Health and Development Neonatal Research Network Centres, and it showed an inverse relationship with birth weight.…”
Section: Short Bowel Syndromementioning
confidence: 99%
See 2 more Smart Citations